To translate the points A, B, and C 3 units to the left, we will subtract 3 from the x-coordinates of each point.
The original coordinates of the points are:
- \( A(2, 3) \)
- \( B(6, 3) \)
- \( C(2, 6) \)
Now, we perform the translation:
-
For point \( A \): \[ A' = (2 - 3, 3) = (-1, 3) \]
-
For point \( B \): \[ B' = (6 - 3, 3) = (3, 3) \]
-
For point \( C \): \[ C' = (2 - 3, 6) = (-1, 6) \]
Now, we label the new points:
- \( A'(-1, 3) \)
- \( B'(3, 3) \)
- \( C'(-1, 6) \)
So the new coordinates after the translation are:
- \( A'(-1, 3) \)
- \( B'(3, 3) \)
- \( C'(-1, 6) \)